Genome-Wide Identification and Characterization of Vacuolar Processing Enzyme Gene Family and Diverse Expression Under Stress in Apple (Malus × Domestic) - Song, Jianfei; Yang, Fei; Xun, Mi; Xu, Longxiao; Tian, Xiaozhi; Zhang, Weiwei; Yang, Hongqiang (Frontiers in Plant Science, 2020)
Abstract: Vacuolar processing enzymes (VPEs) play an important role in stress resistance and development of plants. Despite their diverse roles, little information is available in apple (Malus×domestic). This study firstly presents the genome-wide identification of VPE family genes in apple, resulting in 20 family members those are unevenly distributed across 6 out of the 17 chromosomes. Phylogenetic analysis assigned these genes into four groups. Analysis of exon–intron junctions and motifs of each candidate gene revealed high levels of conservation within and between phylogenetic groups. Cis-element including w box, ABRE, LTR, and TC-rich repeats were found in promoters of MdVPEs. NCBI-GEO database shown that the expression of MdVPEs exhibited diverse patterns in different tissues as well as the infection of Pythium ultimum and Apple Stem Grooving Virus (ASGV). Furthermore, qRT-PCR showed that MdVPE genes were responsive to salinity, cadmium, low-temperature, and drought. Overexpression of MDP0000172014，which was specifically induced by salinity and drought stress, significantly decreased Arabidopsis tolerance to salinity stress. The genome-wide identification and characterization of MdVPEs in apple provided basic information for the potential utilization of MdVPEs in stress resistance.